2008
DOI: 10.1051/0004-6361:20077834
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic anomaly and stratification of Ca in magnetic Ap stars

Abstract: Aims. We have completed an accurate investigation of the Ca isotopic composition and stratification in the atmospheres of 23 magnetic chemically peculiar (Ap) stars of different temperature and magnetic field strength. Methods. With the UVES spectrograph at the 8 m ESO VLT, we have obtained high-resolution spectra of Ap stars in the wavelength range 3000-10 000 Å. Using a detailed spectrum synthesis calculations, we have reproduced a variety of Ca lines in the optical and ultraviolet spectral regions, inferrin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 55 publications
(72 reference statements)
9
75
0
Order By: Relevance
“…Reduction of the UVES spectra was performed with the automatic pipeline (Ballester et al 2000). The reduction process was described in more detail by Kochukhov et al (2006) and Ryabchikova et al (2008).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of the UVES spectra was performed with the automatic pipeline (Ballester et al 2000). The reduction process was described in more detail by Kochukhov et al (2006) and Ryabchikova et al (2008).…”
Section: Observationsmentioning
confidence: 99%
“…However, they did not carry out a stratification analysis but assumed a chemically-homogeneous atmosphere both for the line formation and for model atmosphere calculation. On the other hand, Ryabchikova et al (2008) presented an analysis of the Ca stratification in α Cir based on the model parameters from Kupka et al (1996) and neglecting the influence of chemical gradients on the model structure.…”
Section: Introductionmentioning
confidence: 99%
“…Its light curve displays a small amplitude variation (0.07 mag in V), and it is classified as an α 2 CVn type variable, its variability being caused by the rotation of an inhomogeneous stellar surface. Its measured value of v sin i is 10 km s −1 (Ryabchikova et al 2008), which we verified by performing a synthetic spectrum analysis of UVES and CRIRES data. The optical spectrum displays a richness caused by the rare earth elements, which appears clearly evident at NIR wavelengths as broad but shallow features.…”
Section: Hd 118022 (O Vir) A1pmentioning
confidence: 98%
“…Neodymium is strongly enhanced in the uppermost atmospheric layers according to Paper I. Ryabchikova et al (2008) and demonstrated that Ca, Si, Cr, Fe, Sr, and Ba are concentrated in deep atmospheric layers. One believes that radiatively driven diffusion is one of the main processes responsible for these inhomogeneities.…”
Section: Programs and Model Atmospheresmentioning
confidence: 99%